Iowa Birdline update, December 5, 1994 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Email of the Iowa Birdline update for December 5, 1994. Highlights of the update include a brief sighting of a Barrow's Goldeneye and observations of several other species of Ducks. Also of note were sightings of a Red-throated Loon, a Red Phalarope, Mute Swans, Trumpeter Swans, and four Sandhill Cranes. Also included are handwritten notes for the next week's updates with sightings of a first winter Glaucous Gull and a Bohemian Waxwing. Epson - sheet feed/flatbed